A edição popular no Brasil: o caso da literatura de cordel - Vilma Mota Quintela (Estudos de Literatura Brasileira Contemporânea)
We focus on Brazilian cordel through the point of view of its editing system, highlighting the importance of such popular editing phenomenon that established itself, in Brazil, as a landmark for modernization that changed the relations of cultural production in Northeast Brazil from the last decades of the nineteenth century on. Seen from this perspective, the cordel literature is translated as an effect of modernization that imposed itself in strategic points of the country. The popularization of press, especially in Recife, where first the market for cordel developed, made possible the arising of popular editors who, taking hold of typographic resources then available, were able to, little by little, insert themselves actively in the national cultural market.